Antarctic octopod beaks as proxy for mercury concentrations in soft tissues. (September 2020) - Matias, Ricardo S.; Seco, José; Gregory, Susan; Belchier, Mark; Pereira, Maria E.; Bustamante, Paco; Xavier, José C.
Abstract: As the role of mercury is poorly known in Southern Ocean biota, the total mercury (T-Hg) concentrations were evaluated in upper/lower beaks, digestive gland, gills and mantle muscle of Adelieledone polymorpha and Pareledone turqueti, two of the most abundant octopod species around South Georgia. Beaks had the lowest T-Hg concentrations ( A. polymorpha : [T-Hg]Upper  = 27.2 ± 12.9 ng∙g −1 and [T-Hg]Lower  = 27.5 ± 20.0 ng∙g −1 ; P. turqueti : [T-Hg]Upper  = 34.6 ± 13.9 ng∙g −1 and [T-Hg]Lower  = 56.8 ± 42.0 ng∙g −1 ), followed by gills and muscle. The highest values were recorded in the digestive gland ( A. polymorpha : 251.6 ± 69.7 ng∙g −1 ; P. turqueti : 347.0 ± 177.0 ng∙g −1 ). Significant relationships were found between the concentrations of T-Hg in the beaks and muscle of A. polymorpha (T-Hg in muscle is 10 times higher than in beaks). This study shows that beaks can be used as proxy for T-Hg in muscle for some octopod species, and a helpful tool for estimating total Hg body burden from beaks. Highlights: Bioaccumulation processes involving mercury in Antarctic octopods are poorly known. Antarctic octopod beaks bioaccumulate lower mercury concentrations than soft tissue. The digestive gland presented the highest concentrations of total mercury. Significant relationships between beaks and muscle total mercury concentrations. Beaks can be used to roughly estimate specimen's total mercury body burden.